Evaluating lake charr (Salvelinus namaycush) temperature use in a mountain lake using acoustic telemetry - Leander, Johan (2015)
Bathythermal distribution of lake charr (Salvelinus namaycush) was surveyed in a boreal lake located in northern Sweden. Based on acoustic telemetry, a high resolution dataset was acquired with more than 630 000 observations from eighteen tagged lake charr. The study was conducted during 2013 and 2014 and covered spring, summer and autumn with their contrasting thermal conditions. I found that temperature was a limiting factor for lake charr habitat selection. When given the possibility to choose temperature, i.e. during the thermally stratified summer, they had a preferendum around 8.2°C stretching from 7.5°C to 10.5°C and less than 2% of all detections exceeding 12ºC. Activity of lake charr were, however, at a minimum at these temperatures and instead at maximum levels at depths corresponding to less than 7 and more than 12. Given that activity is correlated to search for prey, this suggest a trade-off between preferred temperatures vs. prey availability.